2011
DOI: 10.1007/s00464-011-1846-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing morbidity and mortality in 100 consecutive minimally invasive esophagectomies

Abstract: Our results support the continued safe use of esophagectomy for selected esophageal diseases, including malignancy. Morbidity, especially wound infection, anastomotic leak, and length of stay is decreasing with the incorporation of minimally invasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 37 publications
3
42
2
6
Order By: Relevance
“…The average LOS for MIE was reported to be 19 days (standard deviation =8 days). In contrast, others including our group have reported a median LOS of 7-8 days (14,15). The authors reported that the rates of major and minor complications were 6.7% and 32.5%, respectively, which is consistent with our own experience (14).…”
supporting
confidence: 55%
“…The average LOS for MIE was reported to be 19 days (standard deviation =8 days). In contrast, others including our group have reported a median LOS of 7-8 days (14,15). The authors reported that the rates of major and minor complications were 6.7% and 32.5%, respectively, which is consistent with our own experience (14).…”
supporting
confidence: 55%
“…Furthermore, patients suffering from esophageal cancer are often elderly with significant comorbidities, which increases the postoperative risks after such a procedure (4). Although, the postoperative mortality after esophagectomy has significantly decreased in high-volume centers over the Original Article Implementation of minimally invasive esophagectomy in a tertiary referral center for esophageal cancer years, high morbidity rates are still recorded (5,6). In an effort to reduce the postoperative morbidity associated with open esophagectomy various minimally invasive esophagectomy (MIE) techniques have been introduced and developed during the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…
years, high morbidity rates are still recorded (5,6). In an effort to reduce the postoperative morbidity associated with open esophagectomy various minimally invasive esophagectomy (MIE) techniques have been introduced and developed during the recent years.
…”
mentioning
confidence: 99%
“…Esophagectomy and esophageal reconstruction is a complex invasive procedure with high morbidity (40%) and mortality (5-10%) rates (1,2). According to previous studies, the presence of comorbidities such as old age, hypertension, diabetes, smoking status, congestive heart failure, coronary artery disease, poor preoperative pulmonary function, and high preoperative serum creatinine level worsens the clinical outcomes including anastomotic leakage, pulmonary complications, and overall survival (2-7).…”
Section: Introductionmentioning
confidence: 99%